Masyarakat Digital dalam Lensa Sosiologi: Dinamika, Tantangan, dan Peluang - Nur Syafika; Nur Riswandy Marsuki; Irsan Irsan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Digital society was born from the process of developing information technology which has formed a new world or new community, namely between the real world and the virtual world (cyber). The aim of this research is to discuss the importance of understanding the challenges and opportunities faced by society. In the use of digital technology, which is increasingly growing rapidly, marked by advances in information and communication technology, it is facing various significant challenges, including the digital divide, privacy and data security issues, as well as disruption of social values. Inequality in access to technology deepens social and economic disparities, while privacy and data security concerns raise concerns regarding the scope of personal information. But digital society also offers great opportunities, such as increased access to information that empowers individuals and groups, and the creation of virtual communities that support social solidarity and innovation. This research uses qualitative methods using data analysis through literature study. The qualitative approach was chosen because this research aims to obtain an understanding and explanation of the phenomenon of digital society with complex and varied challenges and opportunities from the perspective of the subjects involved. Data and information are obtained from various sources, including scientific journals, books, research reports, and online articles.